Vertical market integration and competition : the meat sector in Slovenia - Bojnec, tefan; Günter, Peter (MTT Agrifood Research Finland, 2005)
This paper presents price transmission models explaining the farm-to-retail price spread and degree of competition in the meat marketing chains during the period of economic transition in Slovenia. The meat marketing chains in Slovenia are characterised by relatively large processing and marketing margins, which are expected to decline with market deregulation and integration into the international markets. As results of the economic restructuring and policy reforms, competitive market pressures in a marketing margin determination have increased, inducing pressures for efficiency improvements in the vertical market integration from the farm to the retail stage in the Slovenian meat sector. Co-integration models are applied to estimate vertical market integration and to assess the degree of price competition in the Slovenian beef and pork marketing chains. The tested econometric models confirmed the existence of the long run market integration in the meat chain and the speed of adjustment of price changes. Farm-gate meat prices are identified as weakly exogenous, indicating the crucial role of supply side processing and marketing factors in the retail meat price determination. The results of structural tests suggest a long-run mark-up price strategy in the beef, and a competitive price strategy in the pork, chain as the outcome of policy reforms. The increased competitive market pressures are very likely to increase efficiency in the beef markets. Efficiency improvements in the Slovenian food markets are needed in the increased competitive market pressures of the enlarged European Union markets.
Keywords: Ma; Slovenia; markkinat; matemaattiset mallit; integraatio; kilpailu; hinta; Euroopan unioni; laajennus; agricultural markets; econometric models; co-integration; competition; price strategies; Slovenia; European Union enlargement